Silkpunk Fiction: A Multifaceted Reimagining of Modernity - Xie, Lili; Guo, Guangwei (Advances in Social Sciences Research Journal, 2025)
This paper examines how silkpunk offers a multifaceted reimagining of modernity through its technological imagination, drawing on alternate history, contemporary interpretations of Eastern aesthetics and philosophy, and cultural resistance against Western centrism. Inspired by the historical and cultural heritage of ancient East Asia, Southeast Asia, and the Pacific Islands, silkpunk fiction creates a fantastical world rich with Eastern allure. This approach represents a departure from traditional science fiction narratives, which are predominantly rooted in Western historical and technological frameworks. More than just a literary innovation, silkpunk serves as a form of cultural practice. By reactivating Eastern cultural elements, it integrates critical reflections on technological modernity, ecological ethics, and cultural politics into imaginative storytelling. In doing so, it provides a discursive platform for non-Western perspectives to engage in global visions of the future. Research shows that silkpunk not only diversifies understandings of “modernity” but also expands the boundaries of literary creativity, opening up new imaginative spaces for reflecting on technology, ethics, and cultural identity.